Laporan Kasus: Shigellosis dan Koksidiosis pada Ayam Broiler Berumur 30 Hari di Desa Kutuh, Kuta Selatan, Badung, Bali - Khairunnisa Zahra Ravenska; I Putu Cahyadi Putra; Yeocelin Meida Utami; I Made Kardena; Gusti Ayu Yuniati Kencana (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2026)
Shigellosis is a bacterial infection caused by members of the genus Shigella and is rarely reported in chickens. In contrast, coccidiosis caused by Eimeria spp. is a common and devastating parasitic disease in broiler chicken. Both diseases can cause digestive disorders, decreased performance, and even death, and can potentially occur together under suboptimal rearing conditions. This case report aimed to identify the causative agent of a disease outbreak in broiler chickens on a farm in Kutuh Village through an epidemiological investigation, clinical examination, and a series of laboratory tests. The examination method began with interviews with farmers and field investigations (epidemiology), followed by clinical examination of sick chickens to collect samples and undergo supporting examinations in anatomical pathology, bacteriology, and parasitology laboratories. A 30-day-old broiler chicken showed clinical symptoms of weakness, severe lethargy, decreased appetite, dull and falling feathers, inability to stand, and brownish-yellow diarrhea. Anatomical pathology observations revealed cheilitis in several organs, a fibrin layer on the heart surface, and intestinal bleeding. Histopathological examination revealed the infiltration of polymorphonuclear inflammatory cells in the heart, liver, intestines, and cecum, and the presence of schizonts in the cecal epithelium of infected tissues. Bacteriological examination successfully identified Shigella spp., and parasitological examination revealed Eimeria spp. oocysts in fecal samples, with a total of 273,100 oocysts/gram. Based on these findings, it was concluded that the chickens in this case experienced co-infection with Shigella and Eimeria. Further research on Shigella infection in poultry is recommended, and farmers should improve biosecurity and provide appropriate treatment to their flocks.